Differential Abnormality in Functional Connectivity Density in Preclinical and Early-Stage Alzheimer's Disease - Song, Yu; Wu, Huimin; Chen, Shanshan; Ge, Honglin; Yan, Zheng; Xue, Chen; Qi, Wenzhang; Yuan, Qianqian; Liang, Xuhong; Lin, Xingjian; Chen, Jiu (Frontiers in Aging Neuroscience, 2022)
Background: Both subjective cognitive decline (SCD) and amnestic mild cognitive impairment (aMCI) have a high risk of conversion to Alzheimer's disease (AD). Most of the available evidence described changes in functional connectivity (FC) in SCD and aMCI, while changes in functional connectivity density (FCD) have not been confirmed. Therefore, the purpose of this study was to investigate the specific alterations in resting-state FCD in SCD and aMCI and further assess the extent to which these changes can distinguish the preclinical and early-stage AD. Methods: Total 57 SCD patients, 59 aMCI patients, and 78 healthy controls (HC) were included. The global FCD, local FCD and long-range FCD were calculated for each voxel to identify brain regions with significant FCD alterations. The brain regions with abnormal FCD were then used as regions of interest for FC analysis. In addition, we calculated correlations between neuroimaging alterations and cognitive function and performed receiver-operating characteristic analyses to assess the diagnostic effect of the FCD and FC alterations on SCD and aMCI. Results: FCD mapping revealed significantly increased global FCD in the left parahippocampal gyrus (PHG.L) and increased long-range FCD in the left hippocampus for SCD patents, compared to HCs. However, aMCI patients showed significantly decreased global FCD and long-range FCD in the PHG.L, compared to SCD. The follow-up FC analysis further revealed significant variations between the PHG.L and the occipital lobe in SCD and aMCI patients. In addition, SCD patients also presented significant changes in FC between the left hippocampus and the left cerebellum anterior lobe and inferior temporal gyrus. Moreover, in the SCD and aMCI groups, changes in abnormal indicators were significantly associated with cognitive function. Finally, combining FCD and FC abnormalities allowed for a more precise differentiation of the different clinical stages. Conclusion: To our knowledge, this study is the first to investigate specific alterations in FCD and FC for both SCD and aMCI patients and confirms differential abnormalities which can serve as potential imaging markers for preclinical and early-stage AD. Also, it provides a new insight point for the diagnosis of SCD and aMCI and the determination of disease progression.